Dual task cost in balance control and stability in children from 4–7 years old. Issue 16 (9th December 2020) - Villarrasa-Sapiña, Israel; Estevan, Isaac; Gonzalez, Luis-Millan; Marco-Ahulló, Adrià; García-Massó, Xavier
ABSTRACT: This study analyzed the development of postural control and the cost of the cognitive task on postural control in the bipedal standing position during childhood. Sixty-six normally developed children divided into four groups by age participated in this study. Single (ST) and dual-tasks (DT) were conducted in the bipedal standing position with eyes open. DT included carrying out a cognitive task consisting of a modified Stroop Test. A Wii Balance Board was used to measure postural sway data. The results showed effects of age and condition on postural control ( p  < 0.01). The interaction of age x condition showed that in DT, 4-year-old children presented higher ellipse area than 5, 6, 7-year-olds ( p  < 0.01). Moreover, an effect of age on cognitive performance was found ( p  < 0.001). In conclusion, four-year old children present lower postural control than 5, 6, 7-year-olds. The youngest children gave fewer correct answers than the 6 and 7-year-olds.